Peran Konten Media Sosial dalam Membangun Minat Beli Konsumen: Studi Kualitatif pada Satoe Rasa - Kirana Noor Azillia Prameswara; Abiyyu Pradila Maulidan; Erin Setya Ningtyas; Wihdatul Khoiriyah (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to describe the social media usage strategies employed by Satoe Rasa MSMEs in building their brand and increasing consumer interest, identify the challenges faced, and provide recommendations for more effective digital marketing strategies. The research uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. Data analysis uses Miles and Huberman's thematic analysis model, which includes data reduction, data presentation, and conclusion drawing. The results show that Satoe Rasa utilizes Instagram and TikTok as its main platforms with a diversified content strategy that includes product, location, visitor, and trend content. Social media has proven to be effective in creating Fear of Missing Out (FOMO) and converting digital engagement into physical visits and increased sales. The challenges faced include a lack of consistency in content uploads, limited human resources, and understanding of platform algorithms. The strategies implemented include continuous content evaluation, content diversification, and more structured content planning. This study contributes to the literature on MSME digital marketing by showing that social media not only functions as a means of promotion but also as a tool for building brand identity and influencing consumer purchasing decisions.